1994
DOI: 10.1111/j.1439-0442.1994.tb00132.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Aerobic Capacity and Fitness in Three Different Horse Breeds (Andalusian, Arabian and Anglo‐Arabian)

Abstract: Summary Aerobic capacity and fitness was studied in three different horse breeds (Andalusian, Arabian and Anglo‐Arabian) using a four‐level exercise test of gradually increasing intensity (15, 20, 25 and 30 km/h). The lactate concentration at the first three exercise levels was significantly lower for Arabian and Anglo‐Arabian horses relative to Andalusian horses, but similar for the three breeds at the last level. Arabian and Anglo‐Arabian horses reached a higher rate than Andalusian horses at plasma lactate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 7 publications
(2 reference statements)
1
13
0
1
Order By: Relevance
“…The research presented here was designed in order to elucidate firstly, whether the reduced aerobic capacity in the AN breed, reported in many papers before (Castejón et al 1994;Muñoz et al 1998Muñoz et al , 1999, was due to a limitation in the ventilatory adaptation to exercise, may be in association with the locomotor pattern, and secondly, whether the differences between AN and A breed, are related to the genetic background. In fact, A horses have been traditionally selected for endurance events and they are expected to have a high aerobic capacity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The research presented here was designed in order to elucidate firstly, whether the reduced aerobic capacity in the AN breed, reported in many papers before (Castejón et al 1994;Muñoz et al 1998Muñoz et al , 1999, was due to a limitation in the ventilatory adaptation to exercise, may be in association with the locomotor pattern, and secondly, whether the differences between AN and A breed, are related to the genetic background. In fact, A horses have been traditionally selected for endurance events and they are expected to have a high aerobic capacity.…”
Section: Discussionmentioning
confidence: 97%
“…They found that performance level and aerobic capacity are lower in AN horses, and as a consequence, lower VLA4 (velocity at which blood lactate reaches concentrations of 4 mmol/l) is a common finding (Castejón et al 1994;Muñoz et al 1998Muñoz et al , 1999. Additionally, higher packed cell volume and haemoglobin concentrations were found after an exercise test, because of the combined effects of a greater sweat rate and a greater spleen contraction.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the previous results were presented for Standardbred racehorses, and the age at which an Andalusian horse can be considered physiologically matured is unknown. Although some interbreed comparative studies between foals and adults Andalusian, Anglo-Arabian and Arabian horses have been made (Castejón et al 1994;Rubio et al 1995), no research exists regarding foals and adult Andalusian horses.…”
Section: Discussionmentioning
confidence: 99%
“…Other suitable indices of fitness have included the velocity (V) and heart rate (HR) at a blood lactate concentration of 4 mmol.l -1 i.e. VLa 4 and HR 4 , respectively (Rose et al 1990;Harkins et al 1993;Poso et al 1993;Castejon et al 1994;Misumi et al 1994;Gotlieb-Vedi et al 1995;Persson 1997;Munoz et al 1997;Eaton et al 1999 and others).…”
Section: Horse Exercise Oxygen Uptake Oxygen Debt Energy Consumptmentioning
confidence: 99%